Ergonomic exposure assessment: a study of rater reliability, method reliability, and sampling strategy - Dartt, Angela L., author; Rosecrance, John C., advisor; Chen, Peter Y., committee member; Douphrate, David I., committee member; Brazile, William Joseph, committee member; Gilkey, David P., committee member (Colorado State University. Libraries, 2010)
Poor characterization of exposures due to inadequately tested ergonomics exposure assessment tools contributes to the skepticism regarding the work-relatedness of musculoskeletal disorders. Due to their ability to capture individual exposures for large populations, observational methods have been commonly used to assess awkward postures in occupational settings. However, use of observation-based methods is complicated due to infrequent assessment of reliability and validity. While direct instrumentation is typically recommended for assessment of awkward postures, application of direct instrumentation in large field studies has been limited. Evaluation of reliability, validity, and sampling strategies are critical for ergonomic exposure assessment tools, particularly for research that attempts to establish a causal relationship between ergonomic risk factors and musculoskeletal outcomes. The results of this dissertation research addressed rater reliability, method reliability, and sampling strategy concerns for a computer-based observation tool and direct measurement devices known as an inclinometer. In general, the results from this dissertation research indicated: observation of postures using a video-based assessment tool demonstrated moderate to high inter- and intra-rater reliability for the majority of anatomical areas and body parts evaluated; comparison of a video-based posture assessment tool and inclinometry demonstrated moderate to high correlation for the majority of anatomical areas and body parts evaluated; and, evaluation of sampling strategies of posture assessment using inclinometry demonstrated that two to four hours of sampling may be sufficient when assessing postures of the upper arms and trunk. This dissertation research provided critical information regarding the need for improved exposure assessment techniques in the field of ergonomics.
Department Head: Jac A. Nickoloff.
Keywords: ergonomics; validity; reliability; posture; Human engineering; Health risk assessment; Posture -- Measurement; Musculoskeletal system -- Wounds and injuries